Respuesta :

Answer:

x = -3

y = 0

Step-by-step explanation:

-5x-10y=15  ------->(equation 1)

-5x+10y=15------->(equation 2)

Add (equation 1) and (equation 2)

(-5x-10y) + (-5x+10y) =15 + 15

-5x-10y - 5x + 10y = 30

-5x -5x -10y + 10y = 30

- 10x = 30

x = 30/- 10

x = -3

put x = -3 in (equation 1)

-5(-3) - 10y=15

15 -10y = 15

-10y = 15 - 15

-10y = 0

y = 0/ -10

y = 0

Answer:

(-3,0)

Step-by-step explanation:

-5x-10y=15

-5x+10y=15

Add the two equations together to eliminate y

-5x-10y=15

-5x+10y=15

----------------------

-10x  = 30

Divide each side by -10

10x/-10 = 30/-10

x = -3

Now we need to find y

-5x +10y = 15

-5(-3) +10y = 15

15 +10y = 15

Subtract 15 from each side

15-15 +10y = 15-15

10y =0

Divide each side by 10

10y/10 = 0/10

y=0

(-3,0)